Lunch Lady and the mutant mathletes : Lunch lady bk. 7 - Krosoczka, Jarrett (Lunch lady bk. 07, 2012)
For having skipped the school field trip, Dee, Hector, and Terrence must join the mathletes team but as they are poised to beat the undefeated champions, secret crime fighter Lunch Lady discovers something strange about the opposing team.